The detection of an extremely bright fast radio burst in a phased array feed survey - Bannister, KW; Shannon, RM; Macquart, J-P; Flynn, C; Edwards, PG; O’Neill, M; Osłowski, S; Bailes, M; Zackay, B; Clarke, N; D’Addario, LR; Dodson, R; et al. (IOP Publishing, 2017)
We report the detection of an ultra-bright fast radio burst (FRB) from a modest, 3.4-day pilot survey with the Australian Square Kilometre Array Pathfinder. The survey was conducted in a wide-field fly's-eye configuration using the phased-array-feed technology deployed on the array to instantaneously observe an effective area of 160 deg$^2$, and achieve an exposure totaling 13200 deg$^2$ hr. We constrain the position of FRB 170107 to a region $8'×8'$ in size (90% containment) and its fluence to be 58$±$6 Jy ms. The spectrum of the burst shows a sharp cutoff above 1400 MHz, which could be either due to scintillation or an intrinsic feature of the burst. This confirms the existence of an ultra-bright (>20 Jy ms) population of FRBs.